2 answers:
Answer:
Use the slope formula and slope-intercept form
y
=
m
x
+
b
to find the equation.
f
(
x
)
=
3
x
−
1
Step-by-step explanation:
Answer:
Since we get '2' as an output when we input '0'
So, the function must be increasing the value of x by 2
We see that happen in the second case as well, as our input is incremented by 2
Hence, we can say that
f(x) = x + 2
<em>Kindly Mark Brainly, Thanks </em>
You might be interested in
Isolate the variable by dividing each side by factors that do not contain the variable. 2x=2x-4y+16 2x-16=2x-4y -4y would have to equal -16 Therefore Y=4
Answer:ok
Step-by-step explanation:
Answer:
C. b-4
Step-by-step explanation:
The number -4 shouldn't change since she read 4 fewer books
Answer:C.40
Step-by-step explanation:
Answer:
n
6
Mean
11
Average Absolute Deviation (MAD)
4.6667
Step-by-step explanation: